Optimizing Capital Allocation and Investment Decisions in the U.S. Economy Through Data Analytics (American Journal of Applied Statistics and Economics, 2024)
Today, investment and capital location is a central mechanism of performance in the economic system, but conventional approaches tend to fall short in terms of managing resources, resulting in less than optimal conditions. In the interest of ever increasing availability of big data, advanced data analytics tools integration into capital allocation processes is underdeveloped. This research project fills the gap since it assesses how data analytics can be used to optimize the process of investment decision-making in the U.S. economy. To determine the effect of machine learning, predictive analytics and descriptive analytics tools on capital allocation performance, Return on Investment (ROI), market share change, and financial growth were the primary objectives. There were 300 sampled organizations (both in the public and the private sectors) and the data were gathered by way of surveys, along with secondary financial reports. The data analytics use and the effectiveness of capital allocation were analyzed through Pearson correlation, ANOVA, multiple regressions, and t-tests, as statistical methods. They showed that application of machine learning and predictive analytics was highly linked with the increment in ROI (mean = 19.2%, p < 0.01), the contribution to the growth of market share (mean = 4.8%, p < 0.01), and financial growth (mean = 12.6%, p < 0.01). Moreover, the organizations applying these tools demonstrated better performance in comparison with the ones that did not incorporate data analytics, even emphasizing the impressive role of advanced analytics in achieving better financial performance. These results indicate that a data-driven solution of multiple parties can complement capital allocation and provide high value on economic decisions. The study adds to an emerging knowledge on data analytics applied to economic decisions and aids policymakers and businesses interested in enhancing a company investment strategy.